The Effectiveness of Performance-Based Budgeting in Government Agencies: Can It Lead to Greater Fiscal Responsibility? - Celestin, Mbonigaba; Mishra, Anjay Kumar (Chaturbhujeshwar Academic Journal, 2025)
Performance-based budgeting (PBB) has gained prominence as a key reform mechanism in public financial management, aiming to enhance fiscal responsibility by linking government expenditures to measurable outcomes. This study evalu Chen ates the effectiveness of PBB in government agencies, examining its impact on budget efficiency, fiscal discipline, and transparency from 2020 to 2024. Using a systematic review of empirical studies and statistical analysis, the research identifies key trends in PBB adoption, waste reduction, and financial performance. Findings reveal a strong positive correlation (r = 0.997, p < 0.001) between PBB adoption and fiscal responsibility index scores, increasing from 65 in 2020 to 76 in 2024. Efficiency scores improved from 68 to 78, and outcome achievement rose from 66% to 75%. Wasteful expenditures declined from 5% to 13%, saving approximately 1.3 billion annually. PBB’s effectiveness is limited by political interference, bureaucratic resistance, and unclear performance indicators. The study recommends better digital systems, independent audits, and gradual implementation. By integrating advanced monitoring tools and ensuring greater accountability, PBB can serve as a transformative tool for improving fiscal governance.